Triphora angasi var. leuca Verco 1909 - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Triphora angasi var. leuca Verco, 1909 Triphora angasi var. leuca Verco, 1909: 282. Teretriphora leuca (Verco, 1909) — Cotton & Godfrey 1931: 56. Type locality. Australia, beach at St. Francis Island and Scales Bay on the West Coast. Type material. SAM D.13452, holotype. AMS C.31098, paratypes. Distribution. Australia (Verco 1909; Cotton & Godfrey 1931; Cotton 1959). Remarks. Marshall (1983) considered it to be a junior synonym of Triphoris pallida Pease, 1871. Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 26, DOI:10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536